Evaluation of Air Permeation Behavior of Porous SiC Ceramics Synthesized by Oxidation‐Bonding Technique. Issue 6 (3rd October 2012) - Dey, Atanu; Kayal, Nijhuma; Chakrabarti, Omprakash; Innocentini, Murilo D. M.; Chacon, Welton S.; Coury, José R.
<x xml:space="preserve">Abstract</x> Porous SiC ceramics were synthesized by oxidation bonding of compacts of commercial α‐SiC powder at 1300°C. Different volume fractions of petroleum coke powder were used for variation of porosity of ceramics from 36% to 56%. The material exhibited variations of pore size from 3 to 15 μm, flexural strength from 5.5 to 29.5 MPa, and elastic modulus from 3.3 to 27.6 GPa. Air permeation behavior was studied at 26–650°C. At room temperature Darcian (k1) and non‐Darcian (k2) permeability parameters vary from 1.64 to 18.42 × 10−13 m2 and 0.58 to 2.95 × 10−7 m, respectively. Temperature dependence of permeability was explained from structural changes occurring during test conditions.